Development of Teaching Media Based on Android Application for Floor Gymnastic Blended Learning - Onyas Widianingsih; Muhammad Ishak; Indra Kasih; Sinung Nugroho; Eva Faridah (AL-ISHLAH: Jurnal Pendidikan, 2023)
The objective of this study was to create a novel educational tool in the shape of an Android app for teaching floor gymnastics using blended learning. The research methodology employed is RD research, consisting of 10 stages: (1) Preliminary study, (2) Research planning, (3) Initial product development, (4) Initial (limited) field trials, (5) Revision of limited field test results, (6) Expanded field tests, (7) Revision of field test results, (8) Due diligence, (9) Revision of due diligence results, (10) Dissemination and distribution of the final product. The study was carried out in the Faculty of Sports Science, Medan State University. The research samples included language specialists, media experts, learning experts, and students from both small and big sample sizes. For a sample size of 20 students and a sample size of 75 students. The research utilised expert observation, interviews, and documentation as instruments. The development research utilised t-test analysis for data analysis. This study employs a qualitative technique. The research findings by language experts indicate that the language utilised in the media is highly suitable, achieving a total score of 81% with revisions. According to the first and second media experts, the media used received a total score of 83%, placing it in a highly suitable category for revision. Subsequent media specialists, the media chosen is suitable, receiving a total score of 90% in the highly feasible category. The learning method employed received a total score of 81% from the first and second experts, placing it in the extremely practicable category for modification. Secondary education specialist. The learning utilised a total score of 90% inside a highly achievable category. The small sample achieved a cumulative score of 79% in the relevant area through revision. Extensive samples achieve a 90% rating in the highly usable category. The study's conclusion is that the learning media utilised are highly practical. The results suggest that the learning materials used in this study are very effective and appropriate for their intended purpose. The findings indicate that the chosen learning techniques and resources are appropriate for attaining the intended learning goals.